Fact findings about the frozen buck semen characters freezing with eyc and tris extender and productivity of Black Bengal does as the potential genetic resource in Bangladesh (Research in Agriculture Livestock and Fisheries, 2018)
The research work was conducted at the Artificial Insemination Center under the Department of Animal Breeding and Genetics, Bangladesh Agricultural University, Mymensingh to compare the efficacy between Egg Yolk Citrate (EYC) and Tris diluter for frozen semen production in Black Bengal buck. The parameters of semen characteristics included volume per ejaculate (ml), percentage of individual motility (progressive), normal and live sperm and sperm concentration (billion/ml). After dilution with EYC extender, It revealed from statistical analysis of frozen semen that individual bucks had significant effect (p0.05) on diluted semen motility and motility after cooling with and without glycerol. Motility and morphology of the sperm after equilibration and thawing showed insignificant difference among the bucks using EYC diluter. On the contrary, variation in the motility after equilibration and thawing was found significant (p